Features of individualization and self-development in Western pedagogy (Acta Education, 2024)
The article analyzes the features of individualization and self-improvement in Western pedagogy, based on the ideas of Augustine, Jean-Jacques Rousseau, Immanuel Kant, Friedrich Froebel, Maria Montessori, Janusz Korczak, and Lev Vygotsky. It examines how these thinkers' ideas have shaped modern approaches to education, focusing on personal development, self-awareness, and moral education. Augustine emphasized spiritual self-improvement, Rousseau emphasized the freedom and natural goodness of the child, Kant emphasized education through reason and autonomy, Froebel emphasized the importance of play as a means of development, Montessori emphasized an individual approach to learning, Korczak emphasized respect for children's rights, and Vygotsky emphasized the role of social interaction in development. The article explores these concepts in the context of modern education and provides practical insights on how to implement the principles of individualization and self-improvement in teaching practice.